Moroccan Dirham Flexibilization and Equilibrium Exchange Rate: A Quest for Grail? - Moumni, Nicolas; Dasser, Salma (International Journal of Economics and Financial Issues, 2020)
The purpose of this study is to identify the Moroccan dirham misalignment phases over the period 1998T1-2017T4, related to an estimated equilibrium exchange rate, using an ad hoc Behavioral Equilibrium Exchange Rate (BBER) econometric model. The overvaluation that may result from misalignments is one of the major arguments in the adoption of the flexibility regime by the Moroccan monetary authorities since 2018. We examine the relevance and the validity of the choice of this new regime in the case of Morocco. The observation of the misalignment graph leads us to the following findings: (1) the highest overvaluation is found in the early 2000s, reaching 35% by 2009 and then decreasing until 2012T2; (2) the largest undervaluation of about 15% is observed around 2014; then from the end of 2015, the misalignments did not exceed ± 15%. Keywords: Exchange rate, real equilibrium exchange rate, ARDL JEL Classifications: C 22, F31 DOI: https://doi.org/10.32479/ijefi.9898